Determination of cost of contra-rotating wind turbine with transformer with rotating half - Kovalchuk, Andrii; Khai, Vasyl (Lviv Polytechnic Publishing House, 2015)
For effective use of low-speed potential of a wind use low-power wind turbines with vertical axis of rotation (VAWT). A new design of contra-rotating noncontact VAWT in which two wind rotors rotate in opposite directions is proposed. The contactless transmission of generated power from the multipole permanent magnet synchronous generator (PMSG) and the regulation of electric power carries a special device – a transformer with rotating half (TRH). The cost of VAWT of the classical and offered sample is determined. The offered design of contra-rotating VAWT has till 42 % lower cost than a traditional design of wind turbine with vertical axis of rotation, and this cost advantage grows with reduction of power.
Keywords: contra-rotating wind turbine; wind turbine with a vertical axis of rotation; a transformer with rotating half